ChemInform Abstract: Analysis of Eicosanoids by LC‐MS/MS and GC‐MS/MS: A Historical Retrospect and a Discussion. Issue 34 (26th August 2014) - Tsikas, Dimitrios; Zoerner, Alexander A.
Abstract Review: 72 refs.